Pengaruh Budaya Organisasi dan Motivasi Ekstrinsik Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Dinas Lingkungan Hidup Kabupaten Serang - Maesofhani, Citra Irma; Lutfi, Lutfi (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2019)
The purpose of this study is to describe the effect of organizational culture and extrinsic motivation on job satisfaction to improve employee performance. This research consist of four variables, there are two independent variables (exogen), one dependent variable (endogen), and one intervening variable. The two independent variables are organizational culture and extrinsic motivation. Whereas, the dependent variable is employee performance and the intervening variable is job satisfaction. The sample used in this research are 100 employees at DLH Kab. Serang. The data was collected by distributing questionnaires to respondents. Data were analyzed with SEM (Structural Equation Model) technique by using SmartPLS software. In this research, there are five hypotheses and all of them are accepted. Organizational culture have positive and significant effect on employee performance, extrinsic motivation have positive and significant effect to employee performance, organizational culture have positive and significant effect to job satisfaction, extrinsic motivation have positive and significant effect to job satisfaction, and job satisfaction have a positive and significant effect on employee performance